2015
DOI: 10.1039/c4cs00186a
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification and characterization of photon-upconverting nanoparticles for bioanalytical applications

Abstract: A well-defined surface architecture is essential to generate water-dispersible UCNPs that are long-term stable and enable a wealth of bioanalytical applications.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
348
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 395 publications
(351 citation statements)
references
References 198 publications
(711 reference statements)
0
348
0
3
Order By: Relevance
“…Therefore, surface modification is usually demanded to transfer the hydrophobic NPs into hydrophilic ones with appropriate functional groups (e.g., amino and carboxy) for subsequent bioconjugation ( Figures 3 a and 3b) 17. For this purpose, a number of surface modification strategies have been established, such as ligand exchange, ligand oxidation, ligand‐free synthesis, ligand attraction, electrostatic layer‐by‐layer assembly, and surface silanization 18…”
Section: General Protocols For the Fabrication Of Inorganic Lanthanidmentioning
confidence: 99%
“…Therefore, surface modification is usually demanded to transfer the hydrophobic NPs into hydrophilic ones with appropriate functional groups (e.g., amino and carboxy) for subsequent bioconjugation ( Figures 3 a and 3b) 17. For this purpose, a number of surface modification strategies have been established, such as ligand exchange, ligand oxidation, ligand‐free synthesis, ligand attraction, electrostatic layer‐by‐layer assembly, and surface silanization 18…”
Section: General Protocols For the Fabrication Of Inorganic Lanthanidmentioning
confidence: 99%
“…For a deeper and more detailed description of these matters, some excellent reviews can be found in the recent literature [19,[29][30][31][32][33][34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…37,38 Manipulation of IR radiation using UCNPs has been found to be of much interest because the UV-VIS output can be used to promote several chemical processes or to develop a number of applications in the fields of lighting and displays, energy, photocatalysis, sensing, bioanalytics and theranostics. [39][40][41][42][43][44][45] Up to our knowledge, only two reports concerning the inclusion of UCNPs in self-assembled organogels are available in the literature.…”
Section: Introductionmentioning
confidence: 99%